Korelasi Persebaran Genta Perunggu Dan Candi Di Propinsi Jawa Tengah - Yuniarso K. Adi (Balai Arkeologi Yogyakarta, 1995)
When correlated with the distribution of Hindu-Buddhist temples in the province of Central Java, there appears to be a contradiction. The bell arrtifact, which is a religious ceremony tool for the Hindu Buddhist community, is found mostly in coastal areas, not in hinterlands (only 2 (two)). As we know, temples are places for religious activities where these bells were used, and most temples were found not in coastal area, but in the interiror of Central Java (South Central Java).